2018
DOI: 10.1111/tid.12967
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation for recurrent Clostridium difficile infection in patients with solid organ transplants: an institutional experience and review of the literature

Abstract: Clostridium difficile, an anaerobic gram-positive, spore-forming bacillus, has become the most common cause of nosocomial infectious diarrhea, and is associated with increased mortality in all populations. Patients who have received solid organ transplants (SOT) are at increased risk of Clostridium difficile infection (CDI) and CDI recurrence (rCDI). This may be related to chronic immunosuppression, frequent antibiotic exposure, and increased or prolonged hospitalizations. Increased morbidity and mortality fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 47 publications
(160 reference statements)
1
14
0
Order By: Relevance
“…FMT for the treatment of immunocompromised patients has been met with caution due to the perceived risk of bacterial translocation and sepsis. However, systematic review data suggest that FMT for the treatment of CDI in immunocompromised patients is feasible and safe, describing similar rates of serious adverse events to immunocompetent patients [24,25]. A systematic review identified 44 articles in which FMT had been performed for CDI in 303 immunosuppressed patients.…”
Section: Safety Profile Of Fmt For CDI In Immunocompromised Recipientsmentioning
confidence: 99%
“…FMT for the treatment of immunocompromised patients has been met with caution due to the perceived risk of bacterial translocation and sepsis. However, systematic review data suggest that FMT for the treatment of CDI in immunocompromised patients is feasible and safe, describing similar rates of serious adverse events to immunocompetent patients [24,25]. A systematic review identified 44 articles in which FMT had been performed for CDI in 303 immunosuppressed patients.…”
Section: Safety Profile Of Fmt For CDI In Immunocompromised Recipientsmentioning
confidence: 99%
“…13 However, the transmission of live microorganisms to recipients with underlying illnesses presents a greater potential risk. 14,15 For example, clinicians should consider the possible transmission of the Epstein-Barr virus and cytomegalovirus from donors in immunosuppressed FMT recipients, for which recent guidelines recommend additional donor screening. 16 Several risks are mitigated by implementing a careful selection and screening process for prospective donors.…”
Section: Safety Issue In High-risk Patientsmentioning
confidence: 99%
“…Several clinical trials assessing the role of FMT in the response of patients to CPIs are currently ongoing. While its safety has been demonstrated even in immunocompromised patients, attention should be paid in the future regarding the possible complications of FMT, as some cases of FMT were reported to induce bacteremia through an unclear mechanism [ 112 , 115 ]. Three important points should be considered prior to FMT administration: the screening of the bacterial constituents of the FMT, the removal of harmful pathogens (bacteria, viruses, or parasites), and the possible isolation of cultivation of less abundant but beneficial microorganisms [ 116 ].…”
Section: Gut Microbiota To Overcome Resistance To Cpis In Humansmentioning
confidence: 99%